The Pragmatic Functions of "Nyawit" in Communication on the X Platform - Nugrahani Niken Anindita; Dewi Yufliha Handayani; Falih Saktiandhita Izdihar (Litteratura: Jurnal Bahasa dan Sastra, 2026)
This study examines the use of the term “nyawit” as a pragmatic phenomenon in digital communication on the social media platform X. The study focuses on the pragmatic functions, meanings, and contextual usage of the term “nyawit” in interactions among social media users. The study employs a descriptive qualitative approach with a pragmatic focus. The data consist of 60 utterances containing the word “nyawit,” collected through observation and documentation techniques on the X platform. Data analysis was conducted using the pragmatic correspondence method to uncover the functions and implicatures present in the utterances. The results indicate that the use of “nyawit” is no longer limited to its literal meaning related to oil palm plantation activities but has undergone a pragmatic expansion of meaning. Based on the analysis, seven categories of pragmatic functions were identified: direct criticism or attack, sarcasm or irony, humorous evaluation, self-evaluation, skepticism, metapragmatic functions, and literal meaning. The most dominant function is direct criticism or attack, accounting for 38.3%, indicating that “nyawit” has evolved as an evaluative strategy to assess, reject, or delegitimize utterances deemed illogical and irrelevant. The findings of this study show that digital slang evolves contextually through the collective understanding of social media users and reflects the fast-paced, concise, expressive, and implicit nature of digital communication.   Keywords: Digital slang, social media, nyawit, pragmatics, speech acts